2022
DOI: 10.3390/ijerph19052729
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Enablers to Food Waste Recycling: A Mixed Methods Study amongst UK Citizens

Abstract: We aim to identify influences on UK citizens’ household food waste recycling as a basis for designing strategies to increase household food waste collection rates via local services. Using a UK dataset (n = 1801) and the COM-B (Capability–Opportunity–Motivation–Behaviour) model as a theoretical framework, we conduct quantitative regression and supporting thematic analyses to investigate influences on citizens’ recycling of food waste. Results show that automatic motivation (e.g., emotions and habit) and psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 80 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…This is because citizens already hold positive attitude toward the behaviour, but they may not know how to enforce it because there is no appropriate segregation, collection, and treatment system. We should start creating initiatives to build the capability and the opportunity to perform the behaviour, which is part of the PBC construct [ 78 ]. For example, citizens need to receive bins and bags that would allow them to separate waste.…”
Section: Discussionmentioning
confidence: 99%
“…This is because citizens already hold positive attitude toward the behaviour, but they may not know how to enforce it because there is no appropriate segregation, collection, and treatment system. We should start creating initiatives to build the capability and the opportunity to perform the behaviour, which is part of the PBC construct [ 78 ]. For example, citizens need to receive bins and bags that would allow them to separate waste.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests, however, that more work is needed in this area. Not only are there still many UK citizens who lack access to food waste collection services, many with access still do not engage with these services (Allison et al, 2022). In addition, there is widespread confusion relating to the terms, often used interchangeably, used to label compostable plastics which also leads to confusion regarding their end-of-life management (WRAP, 2007;Allison et al, 2021a).…”
Section: Citizen Engagementmentioning
confidence: 99%
“…There is therefore great value in illustrating the Behavior Change Wheel's application in the present context. Of the few studies in this area, the Behavior Change Wheel has been shown to be a valuable tool for designing interventions targeting recycling (Allison et al, 2022) and reuse (Allison et al, 2021b). It has also been used in behavior change intervention development guides for local and national (England PH, 2020) government and partners therefore making it an appropriate and useful framework for the design of the present intervention.…”
Section: Behavior Changementioning
confidence: 99%
See 2 more Smart Citations